Photonic properties of devices based on multicomponent crystalline compounds with content (Si, Ge, Sn) - Danylchuk, S.P.; Zamurueva, O.V.; Sakhnyuk, V.E.; Fedosov, S.A. (Physics and Chemistry of Solid State, 2021)
The paper presents the results of optical and photoelectric measurements and their analysis for Tl1-xIn1-xDIVxSe2 (DIV – Si, Ge, Sn) crystalline compounds in the wavelength range 0.41.4 μm at a temperature T = 300 K. The work aims to investigate the influence of mole fraction DIVSe2 on the mechanisms of interband transitions and the basic photon parameters of crystals of ТlInSe2–DIVSe2 solid solutions. It was found that the change in the physical properties of the mole fraction of the components x associated with the rearrangement of the band structure significantly expands the functionality of the Tl1-xIn1-x(Si, Ge, Sn)xSe2 (x0.25) crystalline compounds as promising materials for optoelectronic devices.